Implementation of the problem-based learning approach in the Department of Electrical Engineering, University of Malaya - Said, S.M.; Adikan, Faisal Rafiq Mahamd; Mekhilef, Saad; Rahim, N.A. (Taylor & Francis, 2005)
This paper presents the application of the problem-based learning (PBL) method as an innovative approach to teaching engineering. This paper supports the idea that the PBL method is aptly suited to teaching the engineering disciplines, as its methodology nurtures critical thinking and problem-solving skills, which are central to a graduates career in engineering. It elaborates on the implementation of the PBL approach within the Department of Electrical Engineering, University of Malaya. Pertaining issues include the integration of the PBL method into the overall teaching methodology implemented by the department, the role of PBL facilitators and the characteristics of the PBL problems posed in the courses offered. Suggestions for future work, including the necessity for sufficient resources and collaboration with industry and academics from other disciplines, are proposed.